Foraging activity of the re-introduced milky storks (Mycteria cinerea) in Kuala Gula Bird Sanctuary, Perak, Malaysia - Abdul Rahman, Mohd Faid; Ismail, Ahmad; Shohaimi, Shamarina; Omar, Hishamuddin; Hussin, Mohamed Zakaria (Universiti Putra Malaysia Press, 2020)
The milky stork is an endangered waterbird species that is currently being re-introduced in the Kuala Gula Bird Sanctuary, Perak, Malaysia. However, little information is available on the re-introduced populatiońs adaptation and activity especially of that related to foraging. To fill this gap, a new group of re-introduced population released between 2013 and 2014 was followed and studied. During the early release period (January — February 2013), the population incorporated the natural sites (intertidal areas, mudflats, and riverbeds) and also the shrimp farms almost equally as their foraging sites (~50% each). Later (March — May 2013), a shift from the natural foraging sites to the shrimp farms could be observed with increasing visits made to the latter area. However, the storks incorporated the natural sites again between June and August 2013 most notably during their breeding activity. Nonetheless, there was a significant reliance on the newly built shrimp farms (monthly mean visits =17.6 ± 1.26, p = 0.001) and a high percentage of shrimp consumption (30 - 48%) compared to other prey was recorded in the subsequent period (September - June 2014). Furthermore, the principal component analysis (PCA) indicates that the foraging activity of the waterbirds was more likely tied to the area or size of the foraging sites which were heavily influenced by the anthropogenic activity in Kuala Gula. In addition, there is a concern over the prolonged utilization of the shrimp farms and their resource as the milky storks could be exposed to several hazardous pollutants in the long run.